2019
DOI: 10.1177/2050312119875982
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic activity of curcumin through its anti-cancer potential on oral squamous cell carcinoma: A study on Sprague Dawley rat

Abstract: Objectives: Being the most common type of oral malignancies, oral squamous cell carcinoma is initiated by epithelial dysplasia, which can be marked by the expression of nuclear factor kappa B and cyclooxygenase 2. Curcumin has been known for its anti-cancer potential. The objective of this study was to evaluate the anti-cancer potential of curcumin on oral squamous cell carcinoma based on the expression of the nuclear factor kappa B and cyclooxygenase 2 during epithelial dysplasia stage. Methods: This experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Curcumin has the capacity for anti-cancer in oral squamous cell carcinoma dependent on the expression of the nuclear factor kappa B and cyclooxygenase 2 through epithelial dysplasia (Maulina, 2019).…”
Section: Molecular Mechanism Of Curcumin On Oral Cancermentioning
confidence: 99%
“…Curcumin has the capacity for anti-cancer in oral squamous cell carcinoma dependent on the expression of the nuclear factor kappa B and cyclooxygenase 2 through epithelial dysplasia (Maulina, 2019).…”
Section: Molecular Mechanism Of Curcumin On Oral Cancermentioning
confidence: 99%
“…The anticancer activity of curcumin was also explored in 7,12-dimethylbenz­(a)­anthracene-induced oral cancer rat models. It was concluded that the treated group showed a reduction in NF-κB and COX-2 expression as compared with the control . SCC-25 cells, when treated with curcumin, showed decreased cellular proliferation, invasion, and expression of epithelial mesenchymal transition (EMT) markers like, Twist, Snail, and E-cadherin with p53-induced suppression.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…It was concluded that the treated group showed a reduction in NF-κB and COX-2 expression as compared with the control. 111 SCC-25 cells, when treated with curcumin, showed decreased cellular proliferation, invasion, and expression of epithelial mesenchymal transition (EMT) markers like, Twist, Snail, and E-cadherin with p53-induced suppression. This study suggested curcumin to be an adjunctive regimen in the treatment and prevention of oral cancer metastasis.…”
Section: ■ Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that curcumin has an IC 50 value of 10 µM, which reduces the progression and migration of TSCC cells (squamous cell carcinoma of the tongue), inhibits tumorigenesis, and promotes apoptosis [ 70 ]. Curcumin was found to be effective in suppressing cyclooxygenase 2 ( p = 0.03) and NF-κB ( p < 0.01) expression in experimentally induced oral squamous cell carcinoma [ 71 ].…”
Section: Phytoextracts/phytoconstituents For the Treatment Of Oral Cancermentioning
confidence: 99%